Metabolic responses to starvation and feeding contribute to the invasiveness of an emerging pest insect. (January 2021) - Smit, Chantelle; Javal, Marion; Lehmann, Philipp; Terblanche, John S.
Graphical abstract: Highlights: Thermal effects on metabolic parameters were estimated in a novel sugarcane pest. C. newmannii tolerate resource limitations for at least 45 days. Food provision elicits metabolic-temperature responses. Starvation dampens metabolic-temperature effects. Metabolic flexibility may facilitate invasion of novel environments. Abstract: Metabolic rate, and the flexibility thereof, is a complex trait involving several inter-linked variables that can influence animal energetics, behavior, and ultimately, fitness. Metabolic traits respond readily to ambient temperature variation, in some cases increasing relative or absolute energetic costs, while in other cases, depending on the organism's metabolic and behavioral responses to changing conditions, resulting in substantial energy savings. To gain insight into the rapid recent emergence of the indigenous South African longhorn beetle Cacosceles newmannii as a crop pest in sugarcane, a better understanding of its metabolic rate, feeding response, digestion times, and aerobic scope is required, in conjunction with any behavioral responses to food availability or limitation thereof. Here, we therefore experimentally determined metabolic rate, estimated indirectly as CO2 production using flow-through respirometry, in starved, fasted, and fed C. newmannii larvae, at 20 °C and 30 °C. We estimated multiple parameters of metabolic rate (starved, standard, active, and maximum metabolic rates) as well as aerobic scope (AS), specific dynamic action (SDA), and the percentage time active during respirometry trials. Additionally, in individuals that showed cyclic or discontinuous gas exchange patterns, we compared rate, volume, and duration of cycles, and how these were influenced by temperature. Standard and active metabolic rate, and AS and SDA were significantly higher in the larvae measured at 30 °C than those measured at 20 °C. By contrast, starved and maximum metabolic rates and percentage time active were unaffected by temperature. At rest and after digestion was complete, 35% of larvae showed cyclic gas exchange at both temperatures; 5% and 15% showed continuous gas exchange at 20 °C and 30 °C respectively, and 10% and 0% showed discontinuous gas exchange at 20 °C and 30 °C respectively. We propose that the ability of C. newmannii larvae to survive extended periods of resource limitation, combined with a rapid ability to process food upon securing resources, even at cooler conditions that would normally suppress digestion in tropical insects, may have contributed to their ability to feed on diverse low energy resources typical of their host plants, and become pests of, and thrive on, a high energy host plant like sugarcane.